The impact of the minimum wage on the incidence of second job holding in Britain - Helen Robinson; Jonathan Wadsworth (Institute for the Study of Labor (IZA), 2006)
The advent of any earnings boost, such as provided by the introduction of a minimum wage, might be expected to reduce the supply of low paid individuals wanting to hold a second job. This paper uses difference-in-differences estimation on a panel of individuals matched across successive Labour Force Surveys around the time of the introduction of the national minimum wage in the United Kingdom in order to estimate the impact of the minimum wage and its subsequent upratings on second job working. There is little evidence to suggest that the extra pay provided by the introduction of the minimum wage was sufficient to affect the incidence of second job holding significantly. However, hours worked in the main job by second job holders may have risen relative to those not covered by the minimum wage; and hours worked in second jobs may have fallen for those whose second job was initially below the minimum.
urn:nbn:de:101:1-2008071703
Keywords: 330